Answer:
Okay this might be slightly confusing but I'll try to make it simple. x = -10
Explanation:
-4 ( 3x - 7 ) + 5x = -2x + 8 1. get rid of parenthesis first. -4 times 3x = -12x and -4 times -7 is 28
-12x + 28 + 5x = -2x + 8 2. Combine any like terms on each side of the equation. -7x + 28 = -2x + 8 3. Get rid of the smallest x value by adding to both sides -7x
+7x +7x
28 = -2x + 8 4. subtract 8 from both sides to get rid of it. (you wanna get x alone)
-8 -8
20 = -2x 5. Divide both sides by -2 to get 1x (which is x)
/-2 /-2
x = -10